Effect of B30 Palm Oil Methyl Ester Biodiesel with Isobutanol Fuel Additive on Engine Performance of a Diesel Engine - Badrulhisam, Najmi Haziq; Nessiem Ehab Frere; Ismail, Muhammad Yusri; Abdullah, Abdul Adam; W Sawangsri (International Journal of Integrated Engineering, 2024)
Modern society is concerned about pollution and fossil fuel depletion. Many studies examined biodiesel substitution, the renewable diesel fuel known as "biofuel" is derived from materials such as vegetable oils, animal fats, and grease ASTM D7567 describes it. Biodiesel’s ability to run on diesel engines without modification makes it appealing and may affect engine performance and emissions because of its a higher cetane number, less volatility. These qualities can affect diesel combustion and fuel injections lead to less power and higher nitrogen oxides (NOx). Thus, this research uses palm oil and isobutanol fuel additives to boost engine performance and exhaust emissions. This experiment uses fuel samples of 5% 10% 15% 20% isobutanol and POME (B30) in diesel engine and normal diesel as the baseline of the experiment. Brake power, Brake specific fuel consumption, and Torque are the engine performance parameters. Isobutanol can enhance the performance of biodiesel fuel, particularly at higher speeds. B30ISO20 consistently exhibited the highest brake power and lowest brake-specific fuel consumption. The torque of the fuel sample improved with the addition of isobutanol, especially at higher concentrations.